UniqueService platform – Trusted service platform for house chores - Allahyar, Marina; Naseh, Abdulraof; Naeemi, Yasamin; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
The purpose of this paper is to develop a conceptual business model to help needy people by providing them an effective service provider application through mobile and web based platform, called UniqueService. UniqueService is a business model which provides a helpful platform for people to find job easily, without searching around. These services are consisting of house holding and cleaning. People who need to find these kinds of job they can use UniqueService and they will be connected to the job buyers in a short time. There is also an option for helpful or donators who don’t look for money but just want to help old and needy people to get the works done at home. Service buyers consist of people who provide job and service providers are those who are looking for job. “UniqueService” also provides the opportunity for wealthy people by providing them a platform to donate their donation to the needy and unable people. Literature Reviews, benchmarking, Business Model Canvas (BMC), 4 Lenses of Innovation, and Value Proposition Design (VPD) have been used as the methodologies for this paper [1, 2&14].